2009
DOI: 10.1016/s0828-282x(09)70041-8
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor antagonist therapy in congenital heart disease with shunt-associated pulmonary arterial hypertension: A qualitative systematic review

Abstract: BACKGROUND: Congenital heart disease (CHD) with systemic-topulmonary shunting is associated with pulmonary arterial hypertension (PAH). There are similar clinical and pathophysiological features between CHD with shunt-associated PAH and idiopathic PAH. Endothelin-receptor antagonists (ERAs) are oral medications that improve pulmonary hemodynamics, symptoms and functional capacity in many PAH patients. However, the role of ERAs in CHD with shunt-associated PAH is unclear. METHODS: MEDLINE, EMBASE and the Cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…[ 7 , 8 ] A qualitative systematic review about bosentan in adults with PAH-CHD has indicated a significant improvement in exercise capacity (6-minute walk distance [6MWD] and clinical functional class [FC]) and hemodynamic parameters in 2014. [ 9 ] Although it was supported a short-term improvement of ERA in both adults and children with left-to-right shunts while a decline effect at a long-term follow-up. There still are with a lack of systemic analysis about efficiency in both a short-term and a long duration for patients with PAH-CHD.…”
Section: Introductionmentioning
confidence: 96%
“…[ 7 , 8 ] A qualitative systematic review about bosentan in adults with PAH-CHD has indicated a significant improvement in exercise capacity (6-minute walk distance [6MWD] and clinical functional class [FC]) and hemodynamic parameters in 2014. [ 9 ] Although it was supported a short-term improvement of ERA in both adults and children with left-to-right shunts while a decline effect at a long-term follow-up. There still are with a lack of systemic analysis about efficiency in both a short-term and a long duration for patients with PAH-CHD.…”
Section: Introductionmentioning
confidence: 96%
“…4,6,8 Bosentan was the first drug of this class to be approved for the treatment of PAH. 9 Even though it demonstrated to have impact on disease progression and survival (clinical trials BREATHE-1, BREATHE-2, BREATHE-5, and EARLY), [10][11][12] it has been associated with a significant increase in transaminase enzymes levels, which can demand treatment cessation or dose reduction. As so, the structure of bosentan was modified and the new ERA macitentan emerged.…”
Section: Introductionmentioning
confidence: 99%